2012
DOI: 10.3109/17435390.2012.739664
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale reference materials for environmental, health and safety measurements: needs, gaps and opportunities

Abstract: The authors critically reviewed published lists of nano-objects and their physico-chemical properties deemed important for risk assessment and discussed metrological challenges associated with the development of nanoscale reference materials (RMs). Five lists were identified that contained 25 (classes of) nano-objects; only four (gold, silicon dioxide, silver, titanium dioxide) appeared on all lists. Twenty-three properties were identified for characterisation; only (specific) surface area appeared on all list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 49 publications
1
110
0
1
Order By: Relevance
“…As a result, the range of nanomaterial parameters that have to be assessed to characterize nanomaterials is large (Salamon et al, 2010). Aleck Stefaniak has ''summarized twenty-three different physio-chemical material properties that were identified as important for NO characterization as part of the risk assessment process collected from published literature'' (Stefaniak et al, 2012). I have chosen to address nine key characteristics that contribute to the uniqueness of nanomaterials, and these are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the range of nanomaterial parameters that have to be assessed to characterize nanomaterials is large (Salamon et al, 2010). Aleck Stefaniak has ''summarized twenty-three different physio-chemical material properties that were identified as important for NO characterization as part of the risk assessment process collected from published literature'' (Stefaniak et al, 2012). I have chosen to address nine key characteristics that contribute to the uniqueness of nanomaterials, and these are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of proper nanomaterial characterization cannot be understated. Stefaniak et al 5 argues that incomplete nanomaterial characterization limits the reliability (and perhaps validity) of conclusions drawn from scientific investigations, which may impede both future research in and commercialization of nanotechnology. By way of example, a review by Hansen et al 6 of over 400 published nanotoxicology studies concluded that nanomaterial characterization was either poorly described or not at all conducted.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, it is clear that great caution must be taken in the measurement, interpretation and reporting of NM size. For example, the lack of an observed effect of size of a given NM on its toxicity may not support a lack of this relationship.…”
Section: Introductionmentioning
confidence: 99%